Authenticity and Transparency in Sustainable Marketing: Extending the Theory of Planned Behaviour in the rPET Textile Industry - Vaishali Sethi; Virat Banugariya (Canadian Journal of Business, Economics and Health Management, 2026)
This paper aims to discuss sustainability marketing communications focused on the authenticity and transparency of consumer attitudes, trust, and purchase intentions for polyethylene terephthalate (rPET) textiles. The paper is concerned with the material innovation, green communication, and consumer behaviour in the textile industry. The study describes the motivation behind sustainable purchase intention by authenticity and transparency based on the Theory of Planned Behaviour (TPB). A qualitative research strategy and the data were discovered through peer-reviewed journals, reports, and case studies, including Patagonia. Thematic analysis was used to identify trends for the green trust, communication credibility, and behavioural outcomes. These results show that both authentic and transparent sustainability communication have a strong impact on consumer trust, which results in more positive attitudes and purchase intentions towards rPET-based apparel. Also, emotional storytelling and product traceability enhanced consumer confidence for purchase. Overall, the research demonstrates real-life advice to brands and theoretical growth by incorporating communication variables into the TPB framework for sustainable textile marketing.